1989
DOI: 10.1295/polymj.21.655
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Polymerizations of N-Substituted Isomaleimide

Abstract: KEY WORDSAnionic polymerization / Isomaleimide / Styrene / Methyl Methacrylate / Monomer Reactivity Ratios / In order to obtain more detailed information on the polymerization behavior of an unsaturated dibasic acid and its derivatives, particularly five-membered cyclic imides, we investigated the reactivities of N-substituted maleimide, 1 -3 N-( 4-substituted phenyl)isomaleimide,4-6 N-substituted itaconimide, 7 • 8 N-substituted citraconimide, 9 · 10 N-substituted isocitraconimide, 11 and alkyl N-( 4-substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This is consistent with the results of anionic oligomerization of RIMI only with n-BuLi, as reported previously. 4 Molecular weights (M,) for the oligomers were very low and the degrees of polymerization were 3 to 9. The poly(RIMI)s were oligomers.…”
Section: Nmr Ratios Ofrimi/([rimi] + [Rmi]) Werementioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of anionic oligomerization of RIMI only with n-BuLi, as reported previously. 4 Molecular weights (M,) for the oligomers were very low and the degrees of polymerization were 3 to 9. The poly(RIMI)s were oligomers.…”
Section: Nmr Ratios Ofrimi/([rimi] + [Rmi]) Werementioning
confidence: 99%
“…3 It has been reported that anionic polymerizations of N-substituted isomaleimide (RIMI) with n-BuLi give polymers consisting of both structures ofisomaleimide (35--45mol%) and maleimide (65-55 mol%). 4 The resulting polymers were oligomers, and the degrees of polymerization for the poly(RIMI)s were 3 to 7. The specific rotation of the oligo(RIMI) of * To whom all correspondence should be addressed.…”
mentioning
confidence: 99%
“…IM are also compounds of wide interest. They are used in organic synthesis 9, as monomers in oligomers 10, 11, homopolymers 12, or copolymer synthesis 13, or as fungicides and defoliants 14. IM as derivatives of chromophores may be readily coupled to compounds of clinical or biological interest for the detection and measurement of biological compounds 15, 16.…”
Section: Introductionmentioning
confidence: 99%